2022
DOI: 10.3390/rs14163883
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Classification of Martian Chaos Terrains Using Imagery Machine Learning: A Global Distribution of Chaos Linked to Groundwater Circulation, Catastrophic Flooding, and Magmatism on Mars

Abstract: Martian chaos terrains are fractured depressions consisting of block landforms that are often located in source areas of outflow channels. Numerous chaos and chaos-like features have been found on Mars; however, a global-scale classification has not been pursued. Here, we perform recognition and classification of Martian chaos using imagery machine learning. We developed neural network models to classify block landforms commonly found in chaos terrains—which are associated with outflow channels formed by water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Another application example is the detection of volcanic rootless cones (Palafox et al, 2017). Compared with support vector machine approaches, Shozaki et al (2022) demonstrated the recognition and classification of Martian chaotic terrains using convolutional neural network models. Their models showed over 90% accuracy for the classification and contributed to revealing the global distribution of chaos features on Mars.…”
Section: Introductionmentioning
confidence: 99%
“…Another application example is the detection of volcanic rootless cones (Palafox et al, 2017). Compared with support vector machine approaches, Shozaki et al (2022) demonstrated the recognition and classification of Martian chaotic terrains using convolutional neural network models. Their models showed over 90% accuracy for the classification and contributed to revealing the global distribution of chaos features on Mars.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted in order to identify a specific type of Martian landform, such as impact craters [12], dunes [13], dark slope streaks [14], volcanic rootless cones and transverse aeolian ridges [15,16], CO2 jet deposits [17] and chaos terrains [18]. The morphology and distribution, together with material composition analysis, of these landforms can be used to reveal their causes.…”
Section: Introductionmentioning
confidence: 99%